(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Objective: The present study was aimed to evaluate safety and efficacy of two poly herbal formulations Mulmina®Mango and Mulmina® Amla Orange, as supplements in COVID-19 patients when compared to control group that received standard treatment alone. Methodology: Total 120 subjects were divided into 3 arms, each arm of 40 subjects received orally either Mulmina® Mango or Mulmina®Amla Orange along with standard treatment or standard treatment alone, for a period of 28 days. After obtaining the ethics committee approval subjects were screened and only eligible volunteers were enrolled into the study. The subjects were classified as asymptomatic, mildly symptomatic COVID-19 patients and also health care workers who were willing to use the products. In addition to clinical, haematology & serum chemistry parameters, various immune markers like cytokines (serum amyloid A, IL-4, IL-6, IFN-γ, and IgA) and anti-oxidant parameters (SOD, MDA, CAT, GSH) were assessed. Results: There were no drop-outs in this study, the efficacy assessments both from immune and antioxidant parameters prove that the 2 products under investigations, Mulmina® Mango and Mulmina®Amla Orange, have potential and statistically significant (p<0.05) immune boosting (IL-6 &IFN-γ) and anti-oxidant activities (SOD& CAT) in healthcare workers and mild asymptomatic subjects by Day 28. Physician’s assessment and patient feedback also reiterates the same results. Conclusion: From the study results it can be safely concluded that the products Mulmina® Mango and Mulmina® Amla Orange are completely safe for oral administration with good tolerability and also excellent immune boosting & anti-oxidant activities.